A study on the adequacy of the housing development (control and licensing) act 1966 (act 118) in addressing abandoned residential projects / Ili Hasinah Mohamad Fawzi…[et al.] - Mohamad Fawzi, Ili Hasinah; Main, Nurul 'Aqilah Zahrah; Mohd Hashim, Siti Nurzalikha; Ismail, Muhammad Izzhuairi (2011)
An abandoned housing project is one of the biggest problems in the housing industry in Peninsular Malaysia. The Malaysian Government have provided laws and policies to govern housing industry and even with so many amendments had been made, the issue of abandoned houses is yet to be resolved. The real victims are the purchasers themselves. This study discusses the causes of abandoned houses and the adequacy of Housing Development Act (Control and Licensing) 1966 (HDA) in addressing the issue of abandoned houses. From the finding of our study, we found that there are lacunas in the HDA that contribute to the issue of abandoned houses. At the ending part of this study, we propose several recommendations for facing the problems of abandoned housing projects.